STRATEGI DIPLOMASI BUDAYA JEPANG TERHADAP INDONESIA MELALUI ANIME DAN MANGA PADA TAHUN 2018-2021 - Anwar, Aufa Salsabila; Suwecawangsa, Adi Putra; Resen, Putu Titah Kawitri (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 2 No 2 (2023): Jurnal DIKSHI, 2023)
Indonesia and Japan are two countries that have established diplomatic relations for a long time. One of the most prominent collaborations in Japan-Indonesia relations is cultural relations. Indonesia and Japan often conduct cultural exchanges to show a positive image of their country. Anime and manga are popular culture that is often used as Japanese soft power to carry out cultural diplomacy to several countries. Indonesia is a country where people really like anime and manga, that there are even several festivals involving anime and manga every year. In 2018, coinciding with the 60th Japan-Indonesia diplomatic relations, the two countries held a festival to conduct cultural exchanges where Japan often used anime and manga to Indonesia. In 2021, due to the COVID-19 pandemic, Japanese festivals were then held online, one of them, Animeland which is the largest virtual anime festival ever made and held at the year of 2021, in Indonesia. Keywords : Anime-Manga, Cultural Diplomacy, Japan-Indonesia, Soft Power.